Shelf-life Extension of Fig Fruit by Aloe Vera and Basil Oil Coating - Mane, Kavita; Shengole, Ashwini (Current Perspectives in Agriculture and Food Science Vol. 8, 2024)
This study explores the effectiveness of using a coating made from aloe vera and basil oil to prolong the shelf life of fig fruits. Aloe vera, which is an edible, testless substance, forms a protective layer against moisture and air, thereby slowing down fruit ripening and maintaining fruit quality. Basil oil, known for its antimicrobial and antioxidant properties, helps reduce moisture loss, potentially extending fruit shelf life. Fig fruits coated solely with 100 % aloe vera gel persisted for 18 days in storage. However, when treated with both aloe vera and basil oil (at concentrations of 0.05ml and 0.1ml basil oil per 100 ml aloe vera), the fruits exhibited improved outcomes in various aspects such as weight loss (18.01% and 17.03%), TSS (14.33°B and 14.00°B), acidity (0.24% and 2.25%), phenolic content (59.70 mg GAE/100g and 62.02mg GAE/100g)), antioxidant activity (68.04 % and 68.16 %), and microbial count (total plate count-2.0 x 10² to 1.3 x 107 and 1.8 x 10² to 1.1 x 107 CFU/g and yeast and mould count-1.5x10¹ to 6.1x10³ and 2.0x10¹ to 5.9x10³ CFU/g) throughout the storage period, compared to those treated with aloe vera alone. Additionally, figs coated with a combination of 0.05 ml basil oil per 100 ml of aloe vera gel received higher sensory ratings for color, appearance, texture, taste, and overall likability compared to those coated only with aloe vera or treated with 0.1 ml basil oil. Basil oil and aloe vera gel combination increased the shelf life of fig fruits from 6 days to 21 days, indicating that the blend was more effective than using aloe vera gel alone.